The Power Of Words: A Semantic Synonym And Antonym Of Celine Dion’s Song Lyrics - Feras Faswanadina; Namira Salsabila; Yanti Rosalinah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study explores the function of lexical relations, specifically synonyms and antonyms, within the lyrics of Celine Dion’s album Falling into You. Given language’s role in clear communication, the study examines how meaning relationships between words enhance the listener’s emotional and thematic understanding of song lyrics. Focusing on synonymy and antonymy, these relations are seen as key tools in conveying complex emotions and reinforcing the consistency of thematic elements like love, resilience, and growth. Using a descriptive qualitative method, this analysis categorizes and interprets lexical relations found in five songs, presenting findings in a table to showcase the connections between words and their contributions to lyrical depth. The results show that synonyms such as “afraid” and “fear” or “climb” and “rise” introduce layered meanings, expressing emotions like vulnerability or hope. Similarly, antonyms like “found” and “lost” or “you” and “I” highlight contrasts, amplifying both thematic unity and emotional depth. By identifying and interpreting these semantic choices, the study demonstrates how Dion’s lyrics evoke complex emotional responses and strengthen thematic expression. This research highlights the value of semantic analysis in understanding and appreciating the artistry within song lyrics. It advocates for deeper examination of lexical relations in musical texts, providing a framework for linguistics students and enthusiasts to explore the intersections of language, meaning, and emotional expression.